Health situation in the perception of elderly widows assisted by primary health care - Mariana Lustosa de Carvalho; Cristhiano Neiva Santos Barbosa; Valéria Peixoto Bezerra; Ana Maria Ribeiro dos Santos; Cynthia Roberta Dias Torres Silva; Cleidiane Maria Sales de Brito; Maria do Livramento Fortes Figueiredo
ABSTRACT Objective: Analyze the perception of elderly widow women about their health situation. Method: Descriptive and exploratory research, based on qualitative approach performed with 34 widowed women aged 60 years and over, enrolled in primary health care. It was used content analysis in its thematic analysis modality. Results: Three thematic nuclei were obtained: "positive self-perception of health in old age", "negative understanding of health related to the diseases" and "negative repercussions of the absence of the husband in the health situation of the widows". Presence of the family, chronic diseases under control, physical limitations and absence of the partner directly influenced the responses of the elderly widows. Final considerations: The elderly widows perceive their health situation as relatively good and some factors are challenges to a better health situation. For the participants, widowhood means more than just the physical loss of the husband, interfering negatively in the perception of their health situation.